Development of Electronic Documentation System for Final Project with Gamification to Improve the Effectiveness of Final Project Creation - Andre Kurniawan Pamudji (Soegijapranata Catholic University, 2023)
The final project is very important for every student in their educational program. This is a final project that requires in-depth research and thought, helping students put into practice the knowledge they learn and apply it in the form of real work. In several educational programs, the results of the final assignment can also be used as a determining factor for a student's final grade. The process of preparing the final assignment involves several stages, including determining the topic, selecting a supervisor, conducting guidance, conducting a plagiarism test, final assignment exam, and uploading the results of the assignment. end to the existing system. However, in such a long process, if it is not supported by a good system, the process of compiling the Final Project can be a troublesome thing. Therefore, there is a need for a gamification process in the existing system to improve the quality of the system and re-encourage students in doing their final assignments. Gamification uses game design and has several important components such as feature points, badges, levels, leaderboards, challenges and prizes. The gamification process can increase student involvement and the achievements given.